Profil Peresepan Obat Hipertensi pada Pasien Rawat Jalan di Puskesmas X Periode Januari – Juni Tahun 2020 - Hamzah, Hasty; Sapril, Sapril; Irmayana, Irmayana (Jurnal Sains & Kesehatan, 2022)
Hypertension or high blood pressure is a condition in which blood vessels have persistently elevated pressure. This research method is done by collecting data in the form of secondary data. Secondary data was obtained from the Pharmacy section to find out the data on the number of patient visits. The data taken in the form of age group, gender, type of drug, drug class and drug combination. The results showed that the number of prescriptions obtained from January to June was 174 prescriptions and the highest percentage of drug use in hypertension patients based on gender was 115 prescriptions (66.91%) women, namely in the age group 50 years, 96 prescriptions were used. (83.47%), the use of drugs based on Hypertension drugs that was most widely prescribed was Amlodipine with 144 prescriptions (78.68%), the most prescribed group of Hypertension drugs was Calcium Antagonists with 144 (83.75%) prescriptions The most combined drugs were Amlodipine + Captopril with 18 prescriptions (58.06%).